Social Media as a Tool for Political Mobilization: A Case Study of the 2020 Hong Kong Protests - Dong Xinyue (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This research examines the role of social media in political mobilization by analyzing the 2020 Hong Kong protests as a case study. The study utilizes a mixed-methods approach that combines qualitative content analysis of social media posts and interviews with protest participants. The literature review provides a background on the theories of social movements and the use of social media in political activism. The findings show that social media played a critical role in facilitating political mobilization by providing a platform for communication and organization among protesters. The analysis also reveals the limitations and challenges of relying solely on social media for political mobilization. The discussion highlights the implications of these findings for future social movements and political activism.